Jovan Dučić – pesnik o pesništvu (Philologia, 2021)
The text looks at the standpoints of Jovan Ducic, one of the most important poets of Serbian literature. His views on the poetry and poets of his time are expressed in a collection of essays, entitled My Companions. The opinions on poetry and poets are analysed in relation to Ducic’s poetic development. He bases his own views on l’art pour l’art ideas, belief in the perfect artistic expression, the Beauty sufficient for itself.
Keywords: Dučić; esej; pesništvo; pesnici; parnasovstvo; simbolizam; avangarda